Microneedle arrays for vaccine delivery: the possibilities, challenges and use of nanoparticles as a combinatorial approach for enhanced vaccine immunogenicity - Aoife M. Rodgers; Ana Sara Cordeiro; Adrien Kissenpfennig; Ryan F. Donnelly (2018)
Introduction: Vaccination is one of the greatest breakthroughs of modern preventative medicine. Despite this, there remain problems surrounding delivery, efficacy and compliance. Thus, there is a pressing need to develop cost-effective vaccine delivery systems that could expand the use of vaccines, particularly within developing countries. Microneedle (MN) arrays, given their ease of use, painlessness and ability to target skin antigen presenting cells, provide an attractive platform for improved vaccine delivery and efficacy. Studies have demonstrated enhanced immunogenicity with the use of MN in comparison to conventional needle. More recently, dissolving MN have been used for efficient delivery of nanoparticles (NP), as a means to enhance antigen immunogenicity.Areas covered: This review introduces the fields of MN technology and nanotechnology, highlighting the recent advances which have been made with these two technologies combined for enhanced vaccine delivery and efficacy. Some key questions that remain to be addressed for adoption of MN in a clinical setting are also evaluated.Expert opinion: MN-mediated vaccine delivery holds potential for expanding access to vaccines, with individuals in developing countries likely to be the principal beneficiaries. The combinatorial approach of utilizing MN coupled with NP, provides opportunities to enhance the immunogenicity of vaccine antigens.